Brazilian Cultural Heritage and Its Potential for Providing Tourist Experiences through Interpretation - B. Pignaton, Ariadne; C. Santos, José António; Tavares, Mirian (Journal of Tourism, Sustainability and Well-being, 2019)
This paper discusses how interpretation of an artwork can contribute to intensifying heritage tourism experiences, based on an examination of the altarpiece of the former convent of Santo António do Carmo of Olinda, which was designed to promote Catholic triumphalism. The objective is to present the first level of artwork interpretation and highlight the importance of disseminating information about works of art, thereby providing a fuller understanding of their potential role in enhancing heritage tourism’s value. This qualitative, exploratory study included on-site visits and documentary research on the altar’s interpretation. The results suggest that interpretation about artistic objects is important, including key elements such as artistic movements (i.e. chronology), materials used, functions, artwork commissions, artistic affiliations and a brief corresponding description. The findings support the conclusion that interpretation makes tourist attractions more appealing and contributes to tourism development, as well as promoting interest in heritage and strengthening its value.